Analisis Minat Belajar Siswa SD IT Al-Hijrah Terhadap Pelajaran Bahasa Arab - Alfauji Siregar; Anazwa Khairani Dalimunthe; Anis Khairiyah; Kamila Nanda Pertiwi; Muhammad Fadil Azhari; Nazwa Azzahra Sahusilawane; Nia Anggraini; Pitri Aulina Usman Lubis; Sapri (CV. ITTC INDONESIA, 2024)
This research focuses on fourth grade students at SD IT Al-Hijrah, with the aim of analyzing interest in learning Arabic, mufrodat and muhadatsah learning methods, as well as teachers’ efforts to increase students’ interest in learning. The results show that around 90% of fourth grade students at SD IT Al-Hijrah show high interest and enthusiasm in Arabic language lessons, while 10% of students are less interested. Learning methods and teacher efforts vary to maintain diversity and prevent student boredom during Arabic language learning. This research uses qualitative methods with an observation approach, interviews and direct observation at the research site. The results of the research show that students often face obstacles in learning Arabic, especially in reading and understanding it. As a result, interest in learning Arabic is often low